The change - Goldberg, Whoopi, 1955-; Paglia, Jaime (Dark Horse Books, a division of Dark Horse Comics LLC, 2024)
"Isabel Frost is a woman who has spent her life as wife, mother, grandmother--a life she feels isn't all she had hoped for, with a husband who has grown in another direction. A college graduate with a degree in science, Isabel is an amazing gamer, who plays with people all over the country. With the help of her comic-loving grandson and irreverent best friend, she must learn to control her abilities and embrace her new identity as The Change--both the change of life AND her surprising and extraordinary superpowers"--